Enhancing access to justice: the role, challenges, and future of small claims courts in Malaysia - Roslim, Salmah; Mohamad Sirat, Nur Irinah; Musa, Norwahida (Universiti Teknologi MARA, Kedah, 2025)
Small Claims Courts are designed to offer a straightforward and budget-friendly way for people to resolve minor disputes, especially those involving small amounts of money, without navigating the complexities of traditional legal procedures or incurring high costs. These courts focus on everyday issues such as disagreements over contracts, unpaid bills, or disputes between consumers and businesses. They provide a simple, efficient process that allows individuals to present their cases without needing a lawyer. The primary aim of Small Claims Courts is to ensure that justice is accessible and affordable, removing financial and procedural hurdles that might otherwise prevent people from pursuing legal solutions. Establishing the Small Claims Court in Malaysia reflects a broader trend observed in various jurisdictions to enhance access to justice. The court's design allows individuals to pursue claims without the need for legal representation, which is particularly beneficial for those who may not have the financial means to engage in lengthy and costly litigation processes (Niblett & Yoon, 2017). This accessibility ensures that justice is not solely reserved for those with substantial resources, thus promoting a more equitable legal environment (Niblett & Yoon, 2017).